2023
DOI: 10.1111/bjso.12627
|View full text |Cite
|
Sign up to set email alerts
|

‘Guilty as charged’: Intersectionality and accountability in lay talk on discrimination and violence

Abstract: Although intersectionality is gaining ground in social psychological research, most approaches fail to capture the historically and interactionally contingent nature of intersecting identities and the implications of their mobilization. This study, aiming at addressing this lacuna, focuses on the intersection of identities as lay actors' resource, used to account for the murder of Zak Kostopoulos, a young LGBTQI+ activist in Greece. Data are derived from 4 focus group discussions in which 25 young people, aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 79 publications
0
6
0
1
Order By: Relevance
“…According to recent critiques (Phoenix, 2022;Figgou et al, 2023), a great deal of existing research on intersectionality has not managed to avoid some sort of identity essentialism. Although "in theory" authors may explicitly express their commitment to the socially and historically constructed nature of categorization (including gender), "in practice" they pay service to category essentialism.…”
Section: Intersectionality As Participants' Resourcementioning
confidence: 99%
See 2 more Smart Citations
“…According to recent critiques (Phoenix, 2022;Figgou et al, 2023), a great deal of existing research on intersectionality has not managed to avoid some sort of identity essentialism. Although "in theory" authors may explicitly express their commitment to the socially and historically constructed nature of categorization (including gender), "in practice" they pay service to category essentialism.…”
Section: Intersectionality As Participants' Resourcementioning
confidence: 99%
“…Introducing a discursive approach to intersectionality, Figgou et al (2023) maintained that the discursive construction of intersecting identities may be treated as a resource and accomplishment within talk -ininteraction, oriented to social accountability concerns and other rhetorical objectives. Using con cepts provided by discursive/rhetorical psychology in analyzing lay discourse on the murder of Zak Kostopoulos, a LBGTQI+ activist in Greece, these authors indicated that the rhetorical occasioning of intersecting identities may accomplish important positioning work for the speakers.…”
Section: Intersectionality As Participants' Resourcementioning
confidence: 99%
See 1 more Smart Citation
“…Through a discursive analysis of CoG leaders' public argumentation, we complement the existing literature on leadership and risk by considering the dimensions of rhetoric/ideology and of personal/institutional accountability management. Our analysis considers participants' discursive orientation to identity categories (Antaki et al, 1996; Antaki & Widdicombe, 1998), the social action‐functions of identity use in talk (Stokoe & Edwards, 2009) and the personal/institutional accountability management work brought‐off through such orientations (Bozatzis, 2009; Edwards & Potter, 1992; Figgou et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Through a discursive analysis of CoG leaders' public argumentation, we complement the existing literature on leadership and risk by considering the dimensions of rhetoric/ideology and of personal/institutional accountability management. Our analysis considers participants' discursive orientation to identity categories (Antaki et al, 1996;Antaki & Widdicombe, 1998), the social action-functions of identity use in talk (Stokoe & Edwards, 2009) and the personal/institutional accountability management work brought-off through such orientations (Bozatzis, 2009;Edwards & Potter, 1992;Figgou et al, 2023).…”
mentioning
confidence: 99%